Medical Informatics, Statistics and Epidemiology Education: In the Framework of the Tempus-Phare Joint European Project - Zvárová, Jana (Yearbook of Medical Informatics, 1995)
Medicine and health care should react to the changing composition of the population, to diseases and new treatments, to the needs of medical ethics and law, and to changing economic conditions and to social needs. The main goal of health care is to improve the health status of the population. To reach this goal the appropriate use of available information, including for example biomedical knowledge, epidemiological data or patient data, is necessary. The need for education in this field of medical informatics, statistics, and epidemiology is a requirement to solve health-care problems, to develop a long-term perspective and successful functioning of health-care systems. The information sciences can play an important role in promoting the construction of basic data, vocabularies and decision procedures, as well as developing formal methods for problem solving.